2016
DOI: 10.1007/s12185-016-1973-7
|View full text |Cite
|
Sign up to set email alerts
|

Roles of IDH1/2 and TET2 mutations in myeloid disorders

Abstract: Although mutated IDH1/2 are clearly established as oncogenes in myeloid cells, the mechanisms underlying their tumorigenic effects are not clear. Much evidence suggests that mutant IDH enzymes exert their effects via inhibition of TET2, but important clinical differences between IDH1-mutant and TET2-mutant hematopoietic disorders suggest that the oncogenic mechanisms of these mutated enzymes may differ. In particular, divergent effects of mutant IDH1/2 and TET2 on DNA damage repair mechanisms have been identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 57 publications
1
40
0
Order By: Relevance
“…In 2009, two reports showed that the chromosomal region 4q24 in human containing TET2 gene frequently underwent microdeletions and copy number-neutral loss-of-heterozygosity (also named uniparental disomy) in myeloid cancers [35, 36]. Additionally, mutant IDH enzymes can exert their effects via inhibition of TET2, resulting in decreased 5-hmC via the oncometabolite 2 HG [83]. Recently, various reports have showed a high frequency of loss-of-function mutation of the TET2 gene in hematologic malignancies, including MDS, MPN, AML, secondary AML, CMML, and so on [34-42].…”
Section: Tet2 In Human Hematologic Malignanciesmentioning
confidence: 99%
“…In 2009, two reports showed that the chromosomal region 4q24 in human containing TET2 gene frequently underwent microdeletions and copy number-neutral loss-of-heterozygosity (also named uniparental disomy) in myeloid cancers [35, 36]. Additionally, mutant IDH enzymes can exert their effects via inhibition of TET2, resulting in decreased 5-hmC via the oncometabolite 2 HG [83]. Recently, various reports have showed a high frequency of loss-of-function mutation of the TET2 gene in hematologic malignancies, including MDS, MPN, AML, secondary AML, CMML, and so on [34-42].…”
Section: Tet2 In Human Hematologic Malignanciesmentioning
confidence: 99%
“…IDH1/2 (isocitrate deshydrogenase 1/2) mutations are closely associated with higher bone marrow blasts, lower neutrophil counts, and unspecific karyotypes . Mutant IDH1/2 can block myeloid differentiation and increase the accumulation of DNA damage in hematopoietic stem cell/myeloid progenitors leading to oncogenic transformation . IDH1/2 mutations vary from 4% to 12% in patients with MDS and are more common in AML .…”
Section: Epigeneticsmentioning
confidence: 99%
“…Heterozygous, mutually exclusive missense mutations of IDH1/2 have been identified in AML [121], for example the R140G IDH2 mutant in myeloid cell lines [122]. TET2 mutations occur in around 50% of chronic myelomonocytic leukemia (CMML), a subtype of myelodysplastic syndrome/myeloid proliferative neoplasm (MDS/MPN) [124], as well as in around 30% of myeloproliferative neoplasms and AML [125]. Mutations in IDH1/2 and TET2 lead to a decrease in 5-hydroxymethylcytosine (5hmC) and consequently to DNA hypermethylation.…”
Section: Compromised Double Strand Break Repair In Leukemiamentioning
confidence: 99%
“…Mutations in IDH1/2 and TET2 lead to a decrease in 5-hydroxymethylcytosine (5hmC) and consequently to DNA hypermethylation. DNA hypermethylation is in part due to the inhibition of TET2 and the dioxygenases of the AlkB homolog (ALKBH) family, which are Fe (II) and α-ketoglutarate (α-KG)-dependent dioxygenases [126] that repair alkylated DNA [124,127]. When IDH1/2 are mutated, AKLBH enzymes lose their normal catalytic activity and gain activity, which leads to the reduction of α-KG into antagonistic D-2-hydroxyglutarate (D-2-HG), which in turn inhibits the AKLBH dioxygenases [126,128].…”
Section: Compromised Double Strand Break Repair In Leukemiamentioning
confidence: 99%